SOCIO-ECONOMIC CHALLENGES AT CAREGIVING (SPECIAL REFERENCE TO ALZHEIMER’S DISEASE) (Proceedings of the World Disability & Rehabilitation Conference, 2018)
Mental health is not a topic that is usually reconnoitered with an open mind, in Sri Lanka. An astonishingly large of number of people chooses to attribute mental health illnesses to supernatural phenomena. Some people conceal the existence of mental health conditions altogether, because of the humiliation and disgrace associated with these conditions. A dementia condition 50% - 60% is due to the outlook for Alzheimer's disease. The main objective was to identify the challenges confronted by caregivers of dementia patients in the informal care setting. 46 family members from the outdoor patient unit were selected from the Mental Health Unit of Karapitiya Hospital through purposive sampling. The research data were collected by Interviews, Case studies, Observations and Focus Group Discussion. The results showed that during the period of Alzheimer's disease, caregivers experience a range of situations, including: a need to learn about the disease; dealing with guilt; and handling situations of pain, addiction and physical and psychological suffering. In conclusion the study described the challenges of the daily lives of these families, explaining the importance of and highlighting the need to adopt tools and strategies that provide physical, emotional, psychological and financial support to family caregivers of patients with Alzheimer's disease. Social Work intervention in Micro, Mezzo and Macro levels for caregivers are also included in this study. Since the economical challenge is found to be the most defied area in informal care setting, it is necessary for the persons with mental disorders to be entitled with a well-structured state financial assistant equivalent to persons with physical disabilities under the light of National policy on PWDs.
Keywords: stigma; persons with mentally challenged; caregivers; informal care setting